2008
DOI: 10.1063/1.2963714
|View full text |Cite
|
Sign up to set email alerts
|

Design of inexpensive diffraction limited focal plane arrays for millimeter wavelength and terahertz radiation using glow discharge detector pixels

Abstract: Development of focal plane arrays (FPAs) for millimeter wavelength and terahertz radiation is presented in this paper. FPA is based on an inexpensive glow discharge detector (GDD) that serves as a pixel in the FPA. It was shown in previous investigations [A. Abramovich et al., Appl. Opt. 46, 7207 (2007)] that those inexpensive neon indicator lamp GDDs are quite sensitive to millimeter wavelength and terahertz radiation. The diameter of the GDD lamp is 6 mm and thus the FPA can be diffraction limited. Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…Cascade ionization which increases the current in the plasma [7] and enhanced diffusion current that decreases it [8]. This property of the GDD was shown experimentally to be in excellent agreement with the theoretical model of the GDD operation [6][7][8][9][10]. The inexpensive price, high relative response (similar to Golay cells, pyroelectric detectors, bolometers, etc.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Cascade ionization which increases the current in the plasma [7] and enhanced diffusion current that decreases it [8]. This property of the GDD was shown experimentally to be in excellent agreement with the theoretical model of the GDD operation [6][7][8][9][10]. The inexpensive price, high relative response (similar to Golay cells, pyroelectric detectors, bolometers, etc.…”
Section: Introductionsupporting
confidence: 66%
“…), and much faster of response (less than a microsecond), makes such devices excellent candidates for MMW and THz focal plane array imaging, as will be described in this paper. A comparison between the detection capabilities of the GDD to that of a Schottky diode detector was carried-out in [9]. It was found that a GDD commercial neon indicator lamp can be an effective detector in an 0.2 THz imaging system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are investigating heterodyne detection with the GDD in which the NEP is expected to be about two orders of magnitude better. A 4 4 Focal plane array (FPA) based on GDD elements was constructed and tested experimentally [4]. This FPA allow us to capture two dimensional images, but an increase is desirable in data acquisition rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, success in developing less expensive real-time millimeter wave and terahertz imaging systems depends largely on the ability to develop inexpensive focal plane arrays, especially using inexpensive detectors such as GDDs. Indeed, small GDD arrays such as 8 × 8 and 18 × 2 scanner have been developed and tested and found to yield very good image quality despite the large size and dimensions of the lamps [15]- [19]. Recent results include using oversampling sub-pixel shifting to obtain high resolution images [17]- [19] on the order of 0.9 milliradians.…”
Section: Introductionmentioning
confidence: 97%